A Novel Mindful-Compassion Art-Based Therapy for Reducing Burnout and Promoting Resilience Among Healthcare Workers: Findings From a Waitlist Randomized Control Trial - Ho, Andy Hau Yan; Tan-Ho, Geraldine; Ngo, Thuy Anh; Ong, Grace; Chong, Poh Heng; Dignadice, Dennis; Potash, Jordan (Frontiers in Psychology, 2021)
Protecting the mental health of healthcare workers is an urgent global public health priority. Healthcare workers, especially those immersed in palliative care, are prone to burnout due to the intense emotions associated with end-of-life caregiving. This study examines the efficacy of a novel, multimodal, group-based Mindful-Compassion Art-based Therapy (MCAT) that integrates reflective self-awareness with creative emotional expression for protecting healthcare workers’ mental health. A dual-arm open label waitlist Randomized Controlled Trial was conducted. 56 healthcare workers were recruited from the largest homecare hospice in Singapore, and randomized to the immediate-treatment condition of a standardized 6-week, 18-hours MCAT intervention (n=29), or the waitlist-control condition (n=27). Self-administered outcome measures on burnout, resilience, emotional regulation, self-compassion, death attitudes and quality of life were collected at baseline, post-intervention /second-baseline at 6-weeks, and follow-up/post-intervention at 12-weeks. Results from mixed model ANOVAs reveal that treatment group participants experienced significant reduction in mental exhaustion, as well as significant improvements in overall emotional regulation, nonreactivity to intrusive thoughts, approach acceptance of death, and afterlife belief as compared to waitlist-control immediately after MCAT completion. Effect sizes of these impacts ranged from medium to large [η2 = 0.65 to .170]. Results from one-way ANOVAs further reveal that the treatment gains of reduced mental exhaustion and increased emotional regulation were maintained among treatment group participants at 12-weeks follow-up compared to baseline, with new benefits identified. These include increased ability to observe and describe one’s experiences, elevated overall self-compassion, greater mindful awareness, enhanced common humanity, and better quality of life. Effect sizes of these impacts were large [η2 = 0.128 to .298]. These findings reflect the robust effectiveness and positive residual effects of MCAT for reducing burnout, building resilience, nurturing compassion, fostering collegial support, and promoting mental wellness among healthcare workers. The clinical model and applicability of MCAT in larger and more diverse caregiving contexts such as family dementia care are discussed. [ClinicalTrials.gov ID: NCT03440606]